Cholesterol- and lanolin-rich diets may protect against steroid-induced osteonecrosis in rabbits. (December 2013) - Zhao, Garida; Yamamoto, Takuaki; Motomura, Goro; Yamaguchi, Ryosuke; Ikemura, Satoshi; Iwasaki, Kenyu; Iwamoto, Yukihide
<x xml:space="preserve">Abstract</x> Background and purpose It remains controversial how hypercholesterolemia influences the development of steroid-induced osteonecrosis (ON). We investigated the role of hypercholesterolemia induced by a cholesterol-rich diet on the development of ON in rabbits. Methods 40 adult male Japanese white rabbits were randomly divided into 2 groups. 20 rabbits were maintained on a cholesterol-rich diet for 2 weeks before receiving steroid treatment (the CHOL group). The other 20 rabbits were maintained on a standard diet (the control (CTR) group). 2 weeks after the start of the study, all 40 rabbits were injected with methylprednisolone acetate (MPSL) into the right gluteus medius muscle (20 mg/kg body weight). 2 weeks after the steroid injection, both the femora and humeri were examined histopathologically for the presence of ON. Hematological analysis of the serum lipid levels was performed every week. Based on the same protocol, we also investigated the effects of lanolin, a primary component of a cholesterol-rich diet, in another group (the LA group). Results The incidence of ON in the CHOL group (3/20) was lower than that observed in the CTR group (15/20) (p < 0.001). During the whole experiment, the levels of total cholesterol and the ratio of low-density lipoprotein to high-density lipoprotein in the CHOL group were higher than those observed in the CTR group (p < 0.001). The LA group also had a lower incidence of ON (2/20), and the lipid levels in the LA group showed similar changes to those observed in the CHOL group. Interpretation Our findings suggest that preexisting hypercholesterolemia itself induced by a cholesterol-rich diet does not increase the risk of developing steroid-induced ON, but rather seems to diminish it. Lanolin may be the active anti-ON component of the cholesterol diet.